1992
DOI: 10.1021/jo00031a059
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase basicity of hydroxamic acid derivatives

Abstract: mation of the secondary alcohol 6c would be consistent with a transition state, as in 10, again resembling a structure leading to the more stable carbenium ion 12a. In this situation, however, the more stable carbenium ion site is the primary carbon, because the positive charge can be stabilized by carbon-silicon -bond hyperconjugation (12b).19Experimental Section General Procedures. All steps in the preparation, transfer, and main reactions of the organometallic reagents studied here were conducted under an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…for the formohydroxamic acid at the MP2(FC)/6-311++G(d,p)//HF/6-311G(d,p) level. The present result agrees with the conclusion of Decouzon et al, obtained by comparison of FT-ICR results for acetohydroxamic acids and alkyl-substituted amides, regarding preferred protonation on oxygen.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…for the formohydroxamic acid at the MP2(FC)/6-311++G(d,p)//HF/6-311G(d,p) level. The present result agrees with the conclusion of Decouzon et al, obtained by comparison of FT-ICR results for acetohydroxamic acids and alkyl-substituted amides, regarding preferred protonation on oxygen.…”
Section: Resultssupporting
confidence: 93%
“…By similarity with the chemical behavior of amides, it is usually accepted that the protonation site is the carbonyl oxygen ,, rather than the nitrogen or the OH group. However, Fourier transform ion cyclotron resonance (FT-ICR) studies of gas-phase basicities on the acetohydroxamic acid and its N -methyl and O -methyl derivatives do not provide conclusive results. In this context, 14 N NMR measurements on acetohydroxamic acid in aqueous solution seem to support protonation on the oxygen …”
Section: Introductionmentioning
confidence: 99%
“…Gas‐phase basicity of several aliphatic carboxamides has been determined by the equilibrium method in FT‐ICR mass spectrometers (Decouzon et al, ; Homan et al, ; Witt and Grützmacher, ,; Azeim & van der Rest, ). Carboxamides are significantly more basic than their keto homologues as shown by a comparison of the proton affinities of Schemes and .…”
Section: Acids and Derivativesmentioning
confidence: 99%
“…10 kJ/mol than the tabulated value (PA exp ( 1 ) = 834.7 kJ/mol; Hunter & Lias, 1998, ). Gas‐phase basicity of methylated derivatives CH 3 CONHOH, 2 , CH 3 CON(CH 3 )OH, 3 , and CH 3 CONHOCH 3 , 4 were determined by the equilibrium method using FT‐ICR mass spectrometry (Decouzon et al, ). The authors concluded that protonation was also occurring at the carbonyl oxygen, PA values of these three molecules (854, 876, and 879 kJ/mol for 2 , 3 , and 4 , respectively) reflecting the polarizability effect of the methyl group.…”
Section: Acids and Derivativesmentioning
confidence: 99%
“…Negative ion-molecule reactions were monitored as previously described [22] by using the Fouriertransform-ion cyclotron resonance mass spectrometer constructed at the University of Nice-Sophia Antipolis, which has been described elsewhere [23]. Briefly, it consists of Bruker CMS 47 electronics, a Varian IS-in.…”
Section: Gas-phase Acidity Measurementsmentioning
confidence: 99%